Sediment size distribution at three rivers with different types of land use in Endau catchment area, Kluang, Johor, Malaysia - Aweng Eh Rak; Ismid Said; Maketab Mohamed; Liyana Ahmad Afip (African Journals Online, 2016)
Land use along the river will determine the substrate size and distributions. Substrate particle size will inﬂuence aquatic life because substrate is one of the main components forming aquatic habitat. This aquatic habitat is very important in determining river water quality as well as river health. Therefore, identifying the sediment size distribution based on land use is very crucial in river maintenance. Theobjective of this study is to determine the particle size variation between upper reach and lower reach of the sampling station as well as variation from different land use cover at different sub-catchment areas. The pebble counts was conducted at upper reach station and lower reach station by applying the Pebble Count Protocols developed by the West Virginia Department of Environmental Protection and Wolmen Pebble Count Procedure. The average median (D₅₀) for Dengar River ranged between 4.5 mm for upper portion and 2.4 mm for lower portion. Similar observations were found at the Mengkibol River. where particle size ranged between 3.0 mm for upper portion and 2.4 mm for lower portion. As for Madek River which represents land use area for logging activity, the results obtained were different in which the upper portion the particle size was smaller (D₅₀: 4.5 mm) than the lower portion (D₅₀ = 41.5 mm). The ﬁnding of this study will be a basis for river catchment management study and can be used by river management authorities in the country for river management planning.